Discovering English Pre-Service Teachers' Perception of ICT-Based Media Used in ELT - Rivaldo, Muhammad Frederick; Sari, Senorica Yulia (Universitas Negeri Padang, 2025)
This study aimed to explore the perceptions of EFL pre service teachers regarding the use of ICT-based media as a teaching tool. A quantitative, descriptive research design was employed, using a Likert scale questionnaire consisting of 27 positively worded statements across four indicators: interest, concern, object, and environment. Each item was rated on a four-point scale (1 = strongly disagree to 4 = strongly agree). The sample included 106 pre-service teachers. Descriptive statistical analysis was conducted to determine the percentage scores for each indicator. The findings indicate that pre-service teachers generally hold positive perceptions of ICT based media in English language teaching. The highest mean score was in the